Dynamics of the Fermentation Products, Residual Non-structural Carbohydrates, and Bacterial Communities of Wilted and Non-wilted Alfalfa Silage With and Without Lactobacillus plantarum Inoculation - Yang, Fengyuan; Wang, Yanping; Zhao, Shanshan; Feng, Changsong; Fan, Xiaomiao (Frontiers in Microbiology, 2022)
The aim of this study was to investigate effects of wilting and Lactobacillus plantarum inoculation on the dynamics of the fermentation products, residual non-structural carbohydrates, and bacterial communities in alfalfa silage. Fresh and wilted alfalfa were ensiled with and without L. plantarum for 10, 30, 60, and 90 days. A high-throughput sequencing method for absolute quantification of 16S rRNA was adopted to determine the bacterial community composition at different ensiling periods. For the wilted silage, the bacterial community, pH value, and ammonia nitrogen concentration remained stable in the silage at 30 days. L. plantarum inoculation accelerated lactic acid fermentation and altered the predominant genus in the wilted silage as compared with the non-inoculated group. For the non-wilted group, fast consumption of water-soluble carbohydrates was observed at 10 days in the non-inoculated silage along with rapid growth of undesirable Hafnia. L. plantarum inoculation inhibited growth of Hafnia at 10 days in the non-wilted silage. Clostridia fermentation occurred in the non-wilted silage at 90 days, as indicated by an increased pH, formation of butyric acid, and apparent abundance of genera belonging to Clostridia. L. plantarum inoculation inhibited butyric acid accumulation and growth of Garciella in the non-wilted silage at 90 days as compared with the non-wilted silage without inoculation, but had little effect on the growth of Clostridium sensu stricto. Overall, the high moisture content of the non-wilted alfalfa silage led to rapid consumption of water-soluble carbohydrates and growth of harmful microorganisms at the early stage of ensiling, resulting in poor fermentation quality. Wilting and L. plantarum inoculation both improved fermentation quality and inhibited the growth of spoilage microorganisms in alfalfa silage, while L. plantarum inoculation alone failed to achieve optimum fermentation quality of non-wilted alfalfa silage.